Kinetics of the complete combustion of dilute propane and toluene over iron-doped ZrO2 catalyst - Choudhary, Vasant R.; Deshmukh, G. M.; Mishra, D. P. (Energy & Fuels, 2005)
The kinetics of the complete combustion of propane and toluene at very low concentrations in air (0.45 and 0.3 mol % in air, respectively) over iron-doped ZrO2 (cubic) catalyst (Fe/Zr = 0.25) at different temperatures (598-723 K) in kinetic control regime have been investigated. The combustion rate data could be fitted very well to both the power-law and redox (Mars-Van Krevelen) models. However, the redox model provided a better fit to the kinetic data for the propane combustion. It also showed a better fit to the toluene combustion data at the lower temperatures (623 K). The reaction order (with respect to the hydrocarbon), apparent activation energy, and frequency factor (from the power-law model) for the propane combustion were 0.96 (average), 21.16 kcal/mol, and 4.67 x 10(5) Mol g(-1) h(-1) kPa(-n), respectively, and those for the toluene combustion were 0.77 (average), 26.08 kcal/mol, and 1.48 x 10(7) mol g(-1) h(-1) kPa(-n), respectively.